American culture in the 1970s - Kaufman, Will (Twentieth-century American culture., 2009)
The 1970s was one of the most culturally vibrant periods in American history. This book discusses the dominant cultural forms of the 1970s - fiction and poetry; television and drama; film and visual culture; popular music and style; public space and spectacle - and the decade's most influential practitioners and texts: from Toni Morrison to All in the Family, from Diane Arbus to Bruce Springsteen, from M.A.S.H. to Taxi Driver and from disco divas to Vietnam protesters. In response to those who consider the seventies the time of disco, polyester and narcissism, this book rewrites the critical engagement with one of America's most misunderstood decades. Key Features Focused case studies featuring key texts and influential writers, artists, directors and musicians Chronology of 1970s American Culture Bibliographies for each chapter and a general bibliography on 1970s Culture 14 black-and-white illustrations